The Impact of Inflation, Exchange Rate toward Unemployment and Poverty in Indonesia. Case Study of Small and Medium Enterprises at the Tourists’ Area of Lombok - SUPRIYADI, Edy; KAUSAR, Devi Roza Krisnandhi (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017DO - 10.14505//jemt.v8.4(20).11, 2017)
The purpose of the study is to determine the impact of inflation and the weakening of the rupiah exchange rate against US$ toward the level of poverty and unemployment as well as the development of small entrepreneurs. This study uses quantitative and qualitative research methods. The results are as follows: (1) There is significant effect of inflation rate, exchange rate, economic growth and average wages on poverty; (2) There is significant effect of the inflation rate and the average wage on poverty in urban areas; (3) There is significant effect of inflation rate, exchange rate, economic  growth and average wages on poverty in rural areas; (4) There is significant effect of inflation rate, exchange rate and unemployment on unemployment assuming fixed wage; (5) There is no significant effect of inflation rate and exchange rate on unemployment with no fixed wage assumption. The findings of qualitative analysis are as the following: (1) The welfare of both business owners and artisans in small industry are not overly influenced by the impact of inflation and the weakening of rupiah against the US dollar; (2) Strategies to overcome the impact of inflation and exchange rate adopted by small and medium enterprise, include (a ) Efforts to reduce the size of goods (b) reducing the quality of the product (c) reduce business profits and (d) cost efficiency of production; (3) Current marketing system, includes: (a) Waiting for domestic and foreign tourists who visit with tour guides (b) Marketing and selling in designated market established by the government (c) Participation in exhibition (d) Digital marketing through website.